Implementation of Educational Facilities and Infrastructure Standards in Public Islamic Junior High Schools: A Case Study - Aning Puspita Ningrum; Sedya Santosa (Jurnal Isema : Islamic Educational Management, 2026)
Educational facilities and infrastructure play a vital role in supporting learning and improving educational quality. Although the government has established standards, their implementation in schools still faces challenges related to the availability, adequacy, and utilization of facilities. This study aims to analyze the implementation of educational facilities and infrastructure standards at MTs Negeri 1 Magelang and their contribution to learning quality. A descriptive qualitative approach was employed, involving the principal, vice principal for facilities and infrastructure, teachers, and educational support staff. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that most facilities and infrastructure comply with the standards stipulated in Ministry of Education Regulation No. 24 of 2007, including classrooms, science laboratories, libraries, health rooms, places of worship, administrative offices, and sports facilities. These facilities contribute to a comfortable learning environment, effective practical activities, and a conducive educational atmosphere. However, improvements are still needed in updating practical equipment, enhancing arts facilities, and increasing maintenance funding to sustain the quality of educational services.